GI TAGGED INDIGENOUS RICE BEER OF ASSAM AND SOCIO-ECONOMIC EMPOWERMENT OF WOMEN - 1. Brojen Borah , 2. Dr. Mahendra Hazarika (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Rice beer production is an essential socio-economic culture of all the ethnic communities of Assam as well as North-east India. This culture is purely connected to their traditional knowledge which orally passed generation to generation. Generally, the tribal women preserve the technique for their community and produced mainly for household consumption and for cultural rituals. It is also a prime drink offered to guest. After giving recognition by Geographical Indication Tag now the products are opened for global market. The skills and reputation of those women’s, producing the indigenous products get recognised globally. Judima is the first rice beer of North-East India achieving Geographical Indication Tag in 2021. This paper attempted to discuss the role of Geographical indication product Judima of Dimasa community in socio-economic empowerment of rural tribal women of this community.